Penatalaksanan Fisioterapi Pada Kondisi Delay Development di Yayasan Pendidikan Anak Cacat Surakarta - Sodiq, Muh, Agus Widodo, S.Fis, M.Fis (2015)
Background: The problem of child development that are often encountered one of them is Delay Development (DD), it is a significant lag in the physical, cognitive abilities, behavioral, emotional, or social development of a child when compared to a normal child his age, a child with a disorder will be delayed in achieving one or more developmental abilities. Purpose: To determine the benefits of exercise therapy method Neuro Development Treatment (NDT) in improving muscle tone and strength on the right foot and left foot, improving functional ability in patients with DD crawl. Results: After doing therapy 6 times with a duration of 20 to 30 minutes in the first times of therapy, the results obtained for 3 weeks, there has been no increase in leg muscle tone and strength of the right and left, there has been no increase in the ability to crawl. Conclusions: There has been no increase in muscle tone and strength the right leg and left leg, there has been no increase in functional ability to crawl, this is due to time constraints in providing therapy author and not the implementation of the program with a good home. Keywords: Stimulation, Development Delay, Neuro Development Treatment.